Adubação fosfatada na qualidade de sementes e no desempenho agronômico da soja - Ciliprandi, Ana Paula (2019)
The seed is considered a raw material in the soybean production process, with phosphorus being a macronutrient that can contribute positively to its physiological quality, in addition to prospecting for higher yield of crops. The aim of this study was to evaluate the effect of different doses of phosphorus applied via soil on the quality, chemical composition and yield of soybean seeds and, from these, grain yield in the next generation, in different crops. The work was carried out at UTFPR, Campus Dois Vizinhos, in two crops for seed production and evaluation and two subsequent crops for grain production, 16/17 and 17/18; 17/18 and 18/19, respectively. The cultivar used was NS 4823 RR [Marca Registrada]. The treatments applied were: T1 - control, without phosphorus at sowing (0%); T2 - 50% dose of P2O5 recommended by interpretation of soil analysis; T3 - 100% of P2O5 recommended; T4 - 150% of the recommended P2O5 and T5 - 200% of the recommended P2O5. In the field stage, soybean yield and yield components were evaluated for seeds and grains. In the lab, the analyzed variables were: germination, emergence speed index, field emergence, seedling length, accelerated aging dry mass of seedlings, quantification of macro and micronutrients in soybean seeds. The experimental design used in the field was randomized blocks, and in the lab the completely randomized, with three and four replicates, respectively. The data were submitted to analysis of variance, and compared in a two-factor scheme, using regression and for means comparison, Scott Knott, at 5% probability. Increasing doses of phosphorus up to the recommendation, contribute to higher seed yield. Phosphate fertilization in increasing doses contributes to the accumulation of this nutrient in the seeds, and its physiological quality, however, with variable responses between years of cultivation. The conditions of the date of harvest tested, influenced of different manner to quality and quantity of seeds produced. Grain yield is directly influenced by prolonged periods of water deficit, being more sensitive to this factor than to seeds of different quality, provided they have high germination and vigor.